PEMAKNAAN BUDAYA, PESONA DAKWAH DAN DAMPAK SOSIAL: MENELISIK TRADISI SAHUR-SAHUR DI MEMPAWAH KALIMANTAN BARAT - Basuki Wibowo; Muhammad Syaifulloh; Agus Dediansyah; Sahid Hidayat; Ali Akhbar Abaib Mas Rabbani Lubis (Al-Tahrir, 2024)
Abstract: This research explores sahur-sahur tradition (the pre-dawn meal) in Mempawah, which extends beyond being merely a religious ritual, encompassing cultural heritage as well. The study aims to uncover the intricacies of the sahur-sahur tradition, delving not only into the cultural meanings embedded within it but also into the allure of preaching (dakwah) and its positive impact on the social environment. Employing a descriptive-exploratory approach, the research is supported by oral history, collecting data through literature reviews, observations, and in-depth interviews with key figures such as the Custodian of the Amantubillah Palace, Religious Leaders, Community Figures, and the Management of Galaherang Kreasindo in Mempawah. The findings indicate that the sahur-sahur tradition encompasses dimensions of religion, togetherness, and culture, creating a rich cultural legacy. The tradition possesses its own charm of preaching, evolving into a festival sahur (pre-dawn festival) that hosts various activities such as lectures, religious studies, and artistic performances. Its social impact includes enhancing community solidarity, fostering cultural tourism, and stimulating creativity.